Synthesis and Biocidal Activity of Some 5-Thioxo-1,3,4-Oxadiazolo-[3,2-a]-s-Triazine-7-Ones - Andotra, C.S.; Dham, Sumita; Langer, T.C. (Asian Journal of Chemistry, 2010)
N´-(5-Aryl-1,3,4-oxadiazol-2-yl)-N3 -(4-chlorophenyl) ureas on cyclocondensation with carbon disulphide gave 2-aryl-6-(4-chlorophenyl)-5-thioxo-1,3,4-oxadiazolo-[3,2-a ]-s-triazine-7-ones. These compounds were evaluated for antibacterial and antifungal activity.